THE EFFECTIVENESS OF USING PC GAME ENTITLED NANCY DREW IN IMPROVING READING ACHIEVEMENT OF EIGHTH GRADE OF JUNIOR HIGH SCHOOL STUDENTS(An Experimental Study on SLTPN 4 Serang) - Firman Hadiansyah, - (2009)
The research entitled "THE EFFECTIVENESS OF USING PC GAME ENTITLED NANCY DREW IN IMPROVING READING ACHIEVEMENT OF EIGHTH GRADE OF JUNIOR HIGH SCHOOL STUDENTS (An Experimental Study on SLTPN 4 Serang)" was aimed to find out the effectiveness of PC Game in improving reading achievement of eighth grade of junior high school students in SLTPN 4 Serang. The research was conducted by using Quasi-experimental with non equivalent control group design. It involves two classes of eighth grade of SLTPN 4 Serang which were chosen based on purposive sampling. One class acted as control class and the other class acted as experimental class. The data of the research were obtained through pre-test and post-test by using multiple choices of reading comprehension test items. The score from t-test and post-test were computed using SPSS 13 for windows. The computation result from post-test showed that the t obtain (5.643) was higher than t critical (2.00) with p (0.00) < 0.05. It implies that PC game is effective in improving reading achievement of eighth grade of junior high school students